Three essays on families with disability: financial satisfaction, subjective financial well-being, and life satisfaction - Franks Lauderdale, Mitzi Kay (Kansas State University, 2021)
Over 61 million adults in the United States are living with a disability impacting millions of families and their well-being. Caring for and having a disabled/chronically ill family member takes a toll physically, financially, socially, and emotionally on loved ones. These essays use the Midlife in the United States (MIDUS) Refresher data to explore parents and caregivers of disabled/chronically ill loved ones and (a) financial satisfaction among parents, (b) the effect of positive psychology traits on subjective financial well-being among parents, and (c) the impact of subjective financial well-being as a resilience factor among caregivers. The first essay explores subjective financial satisfaction among two populations, parents with disabled/chronically ill children and those with children without disability or chronic illness, using an adaptation of Deacon and Firebaugh’s (1988) input-throughput-output model. Two multinomial logistic regressions were estimated and results showed that families with a disabled/chronically ill child with high thought and effort placed on finances had higher odds of reporting highest financial satisfaction when compared to lowest financial satisfaction but lower odds of having average financial satisfaction when compared to lowest financial satisfaction. Mixed results were found in families with no disabled/chronically ill child. The most significant positive predictors for both populations was perceived control over finances and difficulty arranging life. Next, the second essay examines the effect of positive psychology traits on subjective financial well-being among parents and the effect of having a child with disability/chronic mental illness. Operationalized through Seligman's PERMA constructs, an OLS regression with interaction was employed and results indicated that having a child with a disability/chronic mental illness plays two separate roles. First, there was a main negative effect on subjective financial well-being. There was also a moderating effect, whereby the positive effect of optimism on subjective financial well-being was dependent on the status of having a disabled/chronically ill child. While positive emotions positively predict subjective financial well-being, when considering those with a disabled/chronically ill child, the impact was greater. Finally, the third essay examines the impact of subjective financial well-being as a resilience factor on life satisfaction among caregivers of disabled/chronically ill loved ones. Operationalized using Herrman’s interactive model of resilience (2011), an OLS regression was employed to examine caregivers' life satisfaction across domains through the interactive resiliency model with the inclusion of subjective financial well-being as a personal resiliency resource. This research identifies the importance of considering subjective financial well-being as part of modeling life satisfaction. Subjective financial well-being is not one’s actual financial well-being but rather their perception of their current financial position and looking to the future. Keeping that in mind, subjective financial well-being should be considered by financial planners, financial therapists, and mental health professionals as it serves as a resilience tool in maintaining life satisfaction among caregivers. Collective results imply that financial satisfaction and subjective financial well-being are driven by more than the simple financial resources of income and net worth in families with a disabled/chronically ill child and subjective financial well-being plays a role in life satisfaction among caregivers.
Keywords: Disability; Financial satisfaction; Subjective financial well-being; Positive psychology; Life satisfaction; Caregivers